2004
DOI: 10.1103/physrevb.69.134204
|View full text |Cite
|
Sign up to set email alerts
|

Third-order optical nonlinearity of a transparent glass ceramic containing sodium niobate nanocrystals

Abstract: Measurements of the third-order nonlinear refractive index, n 2 , and the two-photon absorption coefficient, ␣ 2 , of a transparent niobic silicate nanocomposite are reported. Samples with various filling factors, f , of sodium niobate nanocrystals were studied at 1064 nm, 800 nm, and 532 nm. Z-scan and Kerr gate techniques were applied using picosecond and femtosecond lasers. The response time of the nonlinearity was demonstrated to be smaller than 100 fs. An explanation is given for the observed spectral beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 26 publications
3
33
0
2
Order By: Relevance
“…1-10 Different kinds of media, such as polymers, 2 organic liquids, 3 crystals, 4 glass ceramics, 5 nanostructured materials, 6,7 and glasses, [8][9][10][11][12] are currently engineered to possess large nonlinear responses. For instance, it is well known that the presence of heavy-metal ions often increases the nonlinear refractive index of a medium.…”
mentioning
confidence: 99%
“…1-10 Different kinds of media, such as polymers, 2 organic liquids, 3 crystals, 4 glass ceramics, 5 nanostructured materials, 6,7 and glasses, [8][9][10][11][12] are currently engineered to possess large nonlinear responses. For instance, it is well known that the presence of heavy-metal ions often increases the nonlinear refractive index of a medium.…”
mentioning
confidence: 99%
“…Such independence was observed for silver nanoparticles in lead-germanium glass [19]. An explanation for this result can be based on the low concentration of the metallic nanoparticles, once the filling factor has been reported to be an important parameter for the enhancement effect of the optical nonlinearities [20]. In this sense, the magnitude of the nonlinear refractive index shown in Fig.…”
Section: Resultsmentioning
confidence: 65%
“…The old problem of crystal-like orderliness of glass structure arose again in connection with elaboration of glasses suitable for manufacturing EO fibers, high non-linear glass-ceramics and waveguides [36][37][38][39] . Structural sensitive studies of glasses and their crystallization products and Kerr coefficient measurements showed that the high EO sensitivity of a glass was conditioned by the existence of CSGs with stoichiometry of the well-known EO crystals (see Table 1).…”
Section: Electrooptical Sensitivity Of Glassesmentioning
confidence: 99%